Decrease in Admissions and Change in the Diagnostic Landscape in a Newborn Care Unit in Northern Ghana During the COVID-19 Pandemic - Abdul-Mumin, Alhassan; Cotache-Condor, Cesia; Bimpong, Kingsley Appiah; Grimm, Andie; Kpiniong, Mary Joan; Yakubu, Rafiuk Cosmos; Kwarteng, Peter Gyamfi; Fuseini, Yaninga Halwani; Smith, Emily R. (Frontiers in Pediatrics, 2021)
Background: The coronavirus disease (COVID-19) has spread worldwide with an increasing number of patients, including pregnant women and neonates. This study aims to evaluate morbidity and mortality in the COVID-19 era compared to the preceding year in the Neonatal Intensive Care Unit (NICU) at Tamale Teaching Hospital, Ghana. Methods: This is a cross-sectional study carried out on neonates admitted to NICU between March 1st to August 31st, 2019 (pre-COVID-19 era) and March 1st to August 31st, 2020 (COVID-19 era). Multivariate logistic regression was performed to identify predictors of mortality for both periods. Results: From 2,901 neonates, 1,616 (56%) were admitted before, and 1285 (44%) were admitted during the pandemic. Admissions decreased during the COVID-19 era, reaching their lowest point between June and August 2020. Compared to the previous year, during the COVID-19 era, admissions of patients born at TTH, delivered at home, and with infections decreased from 50% to 39%, 7% to 4%, and 22% to 13%, respectively. Referred status (OR=3.3) and vaginal delivery (OR=1.6) were associated with an increased likelihood of mortality. For low- birth weight neonates, admissions of patients born at TTH, with vaginal and home delivery decreased from 62% to 48%, 8% to 2%, and 59% to 52%, respectively. Neonatal infections and congenital anomalies decreased from 8% to 4%, 5% to 3%, respectively. The likelihood of mortality among referred patients increased by 50%. Conclusion: We observed a marked decrease in admissions and change in the diagnosis landscape and related mortality during the pandemic. Underlying challenges, including fear, financing, and health system capacity, might intensify delays and lack of access to newborn care in northern Ghana, leading to higher rates of lifelong disabilities and mortality. Immediate damage control measures, including an improved home-based continuum of care and equipping families to participate in the newborn care with complemented m-health approaches, are needed with urgency.